Cofactors of Pediatric Tinnitus: A Look at the Whole Picture. (March 2019) - Levi, Jessica; Basa, Krystyne; Wong, Kevin; Morlet, Thierry; O'Reilly, Robert
Retrospective chart review of 248 children (1-19 years old) with tinnitus who presented to a tertiary pediatric hospital between 2006 and 2011, looking at which cofactors are predictors of pediatric tinnitus. In our review, we extracted demographics, symptoms, historical data, imaging, and laboratory results; we compared with the general population. Eighty-seven percent had normal hearing. Age distribution, noise exposure, and frequency of psychiatric diagnoses in our cohort were consistent with previous reports. We found a lower incidence of otitis media and the same prevalence of dizziness, asthma, and hearing loss as the general population, a lower prevalence of Eustachian tube dysfunction, otitis media, headaches, and higher incidence of rhinosinusitis. Lack of patient reporting and objective testing complicate the ability to detect pediatric tinnitus. We revealed a gap in the literature regarding rhinosinusitis as a cofactor, imaging during diagnosis, and if psychiatric diagnoses are associated with tinnitus in younger children.